PERBANYAKAN TUNAS Gyrinops versteegii (Gilg.) Domke - Yelnititis Yelnititis (Jurnal Pemuliaan Tanaman Hutan, 2014)
Gyrinops versteegii (Gilg.) Domke) is a member of Thymellaceae having an important role as agarwood source that is potential to develop. Agarwood is a non timber forest product (NTFP) with a high economic value. Gyrinops versteegii (Gilg) Domke was an endemic and rare plants, however, it is cultivated on the island of  Lombok. The study of shoot multiplication from single node stem and cotyledon node explants to shoot  produced was conducted to find out the best method to shoot multiplication. Modification of Murashige and Skoog (MS), Gamborg (B5) dan Woody Plant Medium (WPM) supplemented with 8.0 g/l agar, 30 g/l sucrose and vitamin (0.1 mg/l Thyamine, 0.5 mg/l Nicotinic acid, 0.5 mg/l Pyridoxine dan 2 mg/l Glysin) and 10 g/l myoinositol were used as growth medium treatments. The experiment was conducted on two stages i.e. germination and shoot multiplication. Shoot induction was conducted on modification of MS medium supplemented with Benzyl Adenin (BA) 0.5; 1.0 and1.5 mg/l. The multiplication of shoot conducted on  modification of MS medium, WPM and B5 medium supplemented with 0.5; 0.75 dan 1.0 mg/l Benzyl Adenin (BA). For every treatment there were ten samples (bottles) with one explants in each bottle. The observation was conducted on shoot induction percentage, number of shoot and visual performance of culture. The result showed that modified MS + BA 0.5 mg/l was the best for shoot induction from single node stem explants with the average of 1.6 shoots on 12 weeks. The treatment of modified MS + BA 0.75 mg/l was the best for shoot multiplication from single node stem explants with the average of 5.7 shoots on 12 weeks. The treatment of modified WPM + 0.5 mg/l BA was the best for shoot multiplication from cotyledonery node explants with the average of 4.6 shoots on 12 weeks. The visual performance of shoot resulted was normal.